2020
DOI: 10.1080/13683500.2020.1844641
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the temporal travel choices: a joint modelling of how long to travel and when

Abstract: Many tourism travel decisions are interrelated. From modelling viewpoint incorporating these interrelations is important for understanding the consequences of exogenous shocks, as well as the intended and unintended consequences of policy. This paper addresses two tourist choices in the temporal dimension that were previously only handled as if they were mutually exclusive. The paper adopts a discrete-continuous model framework to simulate tourists' behaviours in selecting travel seasons (choice model) and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Survival rates were higher for those choosing camping as their main form of accommodation, and road transport as their preferred mode of transportation. In terms of decision-making, Li et al [39] used a discrete-continuous model framework to simulate tourist behavior in choosing a travel season (choice model), and the associated travel length of stay (accelerated lapse time model). They established a correlation between the two travel decisions conditional on covariates, finding that seniors' leisure and travel activities were associated with longer air travel and higher income, whereas higher income was associated with a shorter length of stay.…”
Section: Applications Of the Survival Analysis Model In Seniors Tourism Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Survival rates were higher for those choosing camping as their main form of accommodation, and road transport as their preferred mode of transportation. In terms of decision-making, Li et al [39] used a discrete-continuous model framework to simulate tourist behavior in choosing a travel season (choice model), and the associated travel length of stay (accelerated lapse time model). They established a correlation between the two travel decisions conditional on covariates, finding that seniors' leisure and travel activities were associated with longer air travel and higher income, whereas higher income was associated with a shorter length of stay.…”
Section: Applications Of the Survival Analysis Model In Seniors Tourism Researchmentioning
confidence: 99%
“…They established a correlation between the two travel decisions conditional on covariates, finding that seniors' leisure and travel activities were associated with longer air travel and higher income, whereas higher income was associated with a shorter length of stay. Building on the results of previous research (Ashrafi et al [38] and Li et al [39]), this study explored the mechanisms underlying the health effects and mortality risks of travel by seniors using an applied survival analysis model oriented to a longitudinal data cohort on time-to-event orientation.…”
Section: Applications Of the Survival Analysis Model In Seniors Tourism Researchmentioning
confidence: 99%
“…Four variables have been selected to represent tourism behavior, including days of the trip, travel season, travel date, and favorite activity during the trip. Li et al (2021) revealed that tourists' behaviors in selecting travel seasons and the associated trip duration were influenced by a few factors and the correlation between these two tourism decisions was conditional upon the covariates. Dellaert et al (1998) argued that tourists may be restricted by school holidays when choosing the period in which to travel.…”
Section: Participation Decisionmentioning
confidence: 99%